2014
DOI: 10.1159/000360617
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Excitability Changes in Mild Alzheimer's Disease Are Reversed by Donepezil

Abstract: Background: Recent neuroimaging studies in humans support the clinical observations that the motor cortex is affected early in the course of Alzheimer's disease (AD). Methods: We used transcranial magnetic stimulation to measure the active cortical motor threshold (ACMT) in AD patients in the very early stage of the disease, and we explored whether and in which way the pharmacologic manipulation of the cholinergic system could have a direct effect on the excitability of the motor cortex. Results: An increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Some factors could be disease-specific, such as fluctuations in blood glucose levels in T2DM, though, importantly, glucose levels (within the range of 80–200 mg/dL, specified a priori ) were not found to influence variability in the present study. Interestingly, the AD group showed numerically higher reproducibility coefficients for nearly all measures, including RMT, SICI and iTBS aftereffects, which several studies in AD have shown to be abnormal and/or predictive of disease severity or response to treatment ( Liepert et al, 2001 ; Di Lazzaro et al, 2004 ; Koch et al, 2012 , 2015 ; Brem et al, 2013 ; Balla et al, 2014 ). It is possible, however unlikely, that some aspect of the Sham treatment (e.g., daily study visits or interaction with study staff) that the AD group underwent had some stabilizing effect on their neurophysiology.…”
Section: Discussionmentioning
confidence: 95%
“…Some factors could be disease-specific, such as fluctuations in blood glucose levels in T2DM, though, importantly, glucose levels (within the range of 80–200 mg/dL, specified a priori ) were not found to influence variability in the present study. Interestingly, the AD group showed numerically higher reproducibility coefficients for nearly all measures, including RMT, SICI and iTBS aftereffects, which several studies in AD have shown to be abnormal and/or predictive of disease severity or response to treatment ( Liepert et al, 2001 ; Di Lazzaro et al, 2004 ; Koch et al, 2012 , 2015 ; Brem et al, 2013 ; Balla et al, 2014 ). It is possible, however unlikely, that some aspect of the Sham treatment (e.g., daily study visits or interaction with study staff) that the AD group underwent had some stabilizing effect on their neurophysiology.…”
Section: Discussionmentioning
confidence: 95%
“…Dementia can be associated with a progressive deterioration in multiple brain functions [4]. It can sometimes affect cognition, behavior and other psychological functions, and frequently limits mobility [4][5][6]. The risk of dementia increases with age [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia is one of the most common secondary complications and a key cause of mortality in the advanced stages of the disease [14,15]. Deterioration in motor function can also occur in the early stages [6,16,17]. Movement slowness, gait disturbance, postural instability and falls are common [6,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation